THE RELATIONSHIP BETWEEN STUDENTS' PERCEPTIONS OF TEACHER BEHAVIOR ON BEHAVIORISTIC THEORY AND CREATIVITY WITH THE SOCIAL COMPETENCE OF MADRASAH TEACHERS IN AGAM REGENCY - Zet Donny; Ridwan Ridwan; Zaimar Zaimar; Zelhendri Zen (Program Studi PGSD Universitas Flores, 2025)
This research aims to determine the